A safe pair of hands? Bank CEO career experience and acquisition performance - Ahmed, Shaker; Hagendorff, Jens; King, Timothy; Srivastav, Abhishek (Journal of Financial Stability, 2026)
We use the staggered deregulation of interstate banking in the U.S. to show that CEOs who have gained career experience at multiple banks are more likely to pursue acquisitions when competition intensifies. Acquisitions completed by these CEOs perform better than those led by CEOs whose career experience is confined to a single institution. Analyzing the sources of performance gains, we find that CEOs with greater across-bank experience are more effective at identifying and integrating dissimilar targets. Our findings cannot be explained by other formative CEO experiences or a CEO general ability. The results highlight the importance of externally versus internally acquired experience in explaining how managers respond to a competitive shock.